High-performance solution-processed red hyperfluorescent OLEDs based on cibalackrot. Issue 12 (4th January 2022) - Wallwork, Nicholle R.; Mamada, Masashi; Shukla, Atul; McGregor, Sarah K. M.; Adachi, Chihaya; Namdas, Ebinazar B.; Lo, Shih-Chun
Abstract : Solution-processed hyperfluorescent red organic light-emitting diodes with external quantum efficiencies of 15.3% was achieved by using cibalackrot as the fluorescent emitter, where attaching  tert -butyl groups to the assistant host significantly contributes to device performance. Abstract : Hyperfluorescent organic light-emitting diodes (OLEDs) have allowed remarkable device performances to be achieved using fluorescent emitters. Superior device performance has been realised using thermally evaporated emissive layers. However, for future large-scale commercialisation, it is essential to obtain similar device performances using low-cost solution-processing techniques. In the case of hyperfluorescent OLEDs, there remains a delicate interplay of molecular interactions and spacing between the three active components: a host, a thermally activated delayed fluorescent (TADF) assistant host, and a fluorescent emitter. Dispersion of the materials is a dominating factor towards the device efficiencies, making efficient solution-processed devices all the more difficult to achieve. Herein, we have demonstrated solution-processed hyperfluorescent devices with an external quantum efficiency (EQE) of 15.3% using cibalackrot as the fluorescent emitter and 4CzIPN- t Bu as the TADF assistant host in CBP. By studying the use of either 4CzIPN or 4CzIPN- t Bu as the TADF assistant host in both ternary and host-free binary blends, we found that the addition of tert -butyl groups to the TADF material made a significant contribution to the device performance. These sterically hindered groups effectively reduced losses caused by triplet diffusion between the TADF assistant host and the fluorescent emitter by spatially separating adjacent molecules and making a concurrent frontier molecular orbital (FMO) less likely.